The cardioprotective association of average alcohol consumption and ischaemic heart disease: a systematic review and meta-analysis - Roerecke, Michael (2012)
AIMS: Most but not all epidemiological studies suggest a cardioprotective association for low to moderate average alcohol consumption. The objective was to quantify the dose-response relationship between average alcohol consumption and ischaemic heart disease (IHD) stratified by sex and IHD end point (mortality vs. morbidity). METHODS: A systematic search of published studies using electronic databases (1980–2010) identified 44 observational studies (case-control or cohort) reporting a relative risk measure for average alcohol intake in relation to IHD risk. Generalized least-squares trend models were used to derive the best-fitting dose-response curves in stratified continuous meta-analyses. Categorical meta-analyses were used to verify uncertainty for low to moderate levels of consumption in comparison to long-term abstainers. RESULTS: The analyses used 38,627 IHD events (mortality or morbidity) among 957,684 participants. Differential risk curves were found by sex and end point. Although some form of a cardioprotective association was confirmed in all strata, substantial heterogeneity across studies remained unexplained and confidence intervals were relatively wide, in particular for average consumption of 1–2 drinks/day. CONCLUSIONS: A cardioprotective association between alcohol use and ischaemic heart disease cannot be assumed for all drinkers, even at low levels of intake. More evidence on the overall benefit-risk ratio of average alcohol consumption in relation to ischaemic heart disease and other diseases is needed in order to inform the general public or physicians about safe or low-risk drinking levels.